Feasibility study of using the dispersion of surface acoustic wave impulse for viscoelasticity characterization in tissue mimicking phantoms. Issue 1 (18th September 2018) - Zhou, Kanheng; Li, Chunhui; Chen, Siping; Nabi, Ghulam; Huang, Zhihong
Abstract : The aim of this study was to investigate the feasibility of utilizing the phase velocity dispersion of impulse surface acoustic wave (SAW) for viscoelasticity characterization of soft materials. The focused ultrasound transducer and the phase‐sensitive optical coherence tomography were applied as the impulse SAW inducer and tracker, respectively. Three types of liquid‐paraffin‐based cream‐in‐agar phantoms were tested. Phase velocity dispersion curve was extracted using a Fourier transform‐based phase velocity analysis algorithm. Viscoelastic parameters were obtained by fitting the dispersion curve of SAW into Rayleigh wave dispersion equation. The estimated viscoelasticity was compared with that from spherical indenter, ramp‐hold relaxation testing for validation. Both results show an increasing trend in the elasticity and decreasing trend in the viscosity with the concentration of liquid‐paraffin‐based cream increasing in the samples. The proposed method has the capability of evaluating the viscoelastic properties of homogeneous soft tissue. By combining viscoelastic parameters estimated from the proposed method, the dispersive SAW‐impulse‐based viscosity‐compensated elastography could be further developed. Abstract : The feasibility of utilizing the phase velocity dispersion of focus‐ultrasound‐induced impulse surface acoustic wave for viscoelasticity characterization of soft materials was investigated in this study. The proposed technique was demonstrated on various cream‐in‐agar phantoms. The estimated viscoelastic properties from the proposed technique show the same trend with that from the independent spherical indenter, ramp‐hold relaxation test.